Sharia Hotel Business Develovment Strategy in North Sumatera Province - Rijal Allamah Harahap; H.M. Syukri Albani Nasution; Sugianto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to determine the obstacles faced by the Istana IV Syariah Hotel in developing its business and find appropriate solutions and strategies to overcome these obstacles. This research uses the Analytic Network Process (ANP) method with assistance from Super Decisions Software. The research results show that: Internal problems are a priority problem in the sharia hotel business development strategy in North Sumatra Province, then accompanied by external problems. The most priority internal problem based on an expert perspective is HR problems, based on the perspective of sharia hotel practitioners the most priority internal problem is sharia hotel management problems. Based on the expert's perspective, the most priority external problem is the problem of time, while based on the perspective of sharia hotel practitioners, the priority is the MUI policy problem. The priority solution is an internal solution followed by an external solution based on the perspective of sharia hotel experts and practitioners. The internal solution that is a priority according to experts is HR solutions, the same as the external solution that is a priority based on the perspective of sharia hotel practitioners, namely HR solutions. The priority strategy based on the perspective of sharia hotel experts and practitioners is the strategy of not carrying out price wars, followed by the strategy of finding a market niche that suits the hotel, next the strategy of providing services to guests, next the strategy of offering unique experiences to potential guests, then the strategy of collaborating with a travel aggregator, next is an active strategy on social media, next is a strategy to use the power of email marketing, next is a retargeting strategy, next is a strategy for asking for advice and finally a strategy for creating a sharia hotel blog.